PROFIL PENYELESAIAN SOAL HOTS PADA MATERI VOLUME PRISMA OLEH SISWA KELAS VIII SMPN 2 KASIMBAR: Profile of Solving HOTS Questions on Prisma Volume Material by Class VIII Studens of SMPN 2 Kasimbar - Asyita Asyita; Muh. Hasbi; Rita Lefrida; Sukayasa Sukayasa (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This research aims to obtain a description of the profile of solving HOTS questions on prism volume material by class VIII students at SMPN 2 Kasimbar based on Polya's steps. This type of research is qualitative research. The subject in this study consisted of one student with high mathematical ability (DA) who was selected from the results of a grouping based on his mathematical ability, then the subject was willing and able to communicate well and was recommended by the mathematics teacher at the school. The results of the research show that the HOTS problem solving profile of high ability (DA) students in solving HOTS volume prism problems is: 1) at the stage of understanding the problem, the DA subject writes down what is known and is asked in the question based on the information he obtained in the question, 2) makes a plan , the DA subject prepares a plan by linking the knowledge he has and the information he obtains to the problem, so that the DA subject prepares a solution plan correctly. 3) carry out the plan, the DA subject carries out the solution plan according to the plan and uses his numeracy skills to get the correct answer. 4) at the stage of re-checking the answer, the DA subject re-checks the answer by carrying out proof and also making a conclusion at the end of the proof. So that DA meets the four indicators that have been presented.